Enhancing students’ skills in writing sentences and paragraph construction through the J-Match And J-Mix Programs: an innovation through call methodology / Nely Anthony - Anthony, Nely (2006)
This study aims to determine the effectiveness of using the J-Match and J-Mix programs in enhancing the writing skills among the Year 4 students of SK Semenggok, Padawan, especially in relation to their sentences and texts construction. Both tools are the main components in the Hot Potato program which are interactive in nature and they are deemed effective in teaching the various skills of writing in ESL. Computer technology has been used for many years in language teaching and learning especially in the western countries but the usage ofsuch technology in the Malaysian classrooms is only becoming more prominent, notably after the introduction of the teaching of Science and Mathematics in the English language begining in the year 2002. Besides that, this study serves to prove that teachers can be creative and innovative by inventing teaching tools that suit their students' ability. The success of the two tools in enhancing writing among the particular group ofstudents shows that writing can be taught by the innovtive use of technology. Therefore, its inclusion and application into the Malaysian classrooms scenario should be ammicably embraced.